Frontline workers in education, health and welfare: how much do they earn in European countries? A comparative income analysis based on the EU-LFS - René Lehwess-Litzmann (Soziologisches Forschungsinstitut Göttingen (SOFI), 2022)
The present paper analyses frontline workers' incomes in the fields of education, health, and welfare (“EHW”). In the face of an upsurge in demand for such services, the question is how EHW occupations can attract enough qualified workers, now and in the future. In public perception, EHW work is poorly paid, while empirically, wage heterogeneity between occupations is quite large. A comprehensive comparison of EHW occupations' wages across Europe is still lacking. The present contribution seeks to fill this gap by comparing incomes for 24 European countries, based on data from the European Union's labour force survey (EU-LFS) between 2016 and 2020. Our descriptive analysis yields that EHW workers earn slightly above-average incomes in the majority of countries. This result can be explained by the high share of EHW workers with a tertiary education level. By contrast, for EHW workers with only secondary education, we find that they earn less in EHW than in other labour-market segments. Both outside and inside the EHW, we observe higher incomes for men than for women. Between EHW occupations, there is an income hierarchy led by medical doctors and tertiary education teachers. At the lower end, there are personal care workers with lower formal education who earn below-average incomes in all observed countries. Yet the degree to which they are penalised differs widely. From a dynamic perspective, our findings hint at a slightly deteriorating relative income position of EHW workers in the 2010s, apparently caused less by declining wages than by structural change in the wider labour market. – – In diesem Working Paper werden Einkommen von Beschäftigten in den Bereichen Bildung, Gesundheit und Soziales (,,EHW“) analysiert. Angesichts der steigenden Nachfrage nach solchen Dienstleistungen stellt sich die Frage, wie EHW-Berufe jetzt und in Zukunft genügend qualifizierte Arbeitskräfte anziehen können. In der öffentlichen Wahrnehmung ist Arbeit in diesen Bereichen schlecht bezahlt, während empirisch eher Lohnheterogenität beobachtbar ist. Ein umfassender Vergleich der Löhne von EHW-Berufen in ganz Europa steht noch aus. Der vorliegende Beitrag untersucht auf Basis der Arbeitskräfteerhebung der Europäischen Union (EU-AKE) Einkommen in 24 europäischen Ländern in den Jahren 2016 bis 2020. Es zeigt sich, dass EHW-Beschäftigte in der Mehrzahl dieser Länder leicht überdurchschnittliche Einkommen erzielen. Dies lässt sich durch den hohen Anteil von EHW-Beschäftigten mit einem tertiären Bildungsniveau erklären. Im Gegensatz dazu stellen wir fest, dass EHW-Beschäftigte, die nur über einen Sekundarschulabschluss verfügen, in den Bereichen Bildung, Gesundheit und Soziales weniger verdienen als anderswo. Sowohl außerhalb als auch innerhalb dieser Bereiche beobachten wir höhere Einkommen für Männer als für Frauen. Zwischen EHW-Berufen gibt es eine Einkommenshierarchie, die von Ärzten und Hochschullehrern angeführt wird. Am unteren Ende befinden sich Pflegekräfte mit wenig formaler Qualifikation, die in allen beobachteten Ländern unterdurchschnittliche Einkommen erzielen. Das Ausmaß der Benachteiligung ist jedoch sehr unterschiedlich. Unsere Ergebnisse deuten ferner darauf hin, dass sich die relative Einkommensposition von EHW-Beschäftigten in den 2010er Jahren leicht verschlechtert hat, was offenbar weniger auf sinkende Löhne als auf strukturelle Veränderungen im Arbeitsmarkt insgesamt zurückzuführen ist.
Keywords: 330; income; care work; inequality; Europe